2020
DOI: 10.1186/s12931-020-01383-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeted lung denervation in sheep: durability of denervation and long-term histologic effects on bronchial wall and peribronchial structures

Abstract: Background: Targeted lung denervation (TLD), a novel bronchoscopic procedure which attenuates pulmonary nerve input to the lung to reduce the clinical consequences of neural hyperactivity, may be an important emerging treatment for COPD. While procedural safety and impact on clinical outcomes have recently been reported, the mechanism of action has not been reported. We explored the long-term pathologic and histopathologic effects in a sheep model of ablation of bronchial branches of the vagus nerve using a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In this study, efferent axon staining was decreased by >70% at 365 and 640 days. Furthermore, tissue structure 1 cm proximal and distal to the treated area remained normal and there were no serious effects in the pulmonary veins and arteries and the oesophagus [34].…”
Section: Published Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study, efferent axon staining was decreased by >70% at 365 and 640 days. Furthermore, tissue structure 1 cm proximal and distal to the treated area remained normal and there were no serious effects in the pulmonary veins and arteries and the oesophagus [34].…”
Section: Published Resultsmentioning
confidence: 88%
“…Pre-clinical studies Before patient testing, multiple bench and animal studies were performed, two using the same system and power used in the clinical trials [33,34]. The first study was performed in 11 sheep and two dogs and showed that the treatment reduced pulmonary airway resistance, abolished the Hering-Breuer reflex and consistently resulted in bronchial wall fibrosis to a depth which engulfed nearly all pulmonary branches of the vagal nerve [33].…”
Section: Published Resultsmentioning
confidence: 99%
“…TLD could have the advantage over pharmacologic treatments that it targets the nerve directly, but still it is questionable whether all nerve branches can be reached and what the sustainability of the treatment is, with regard to, for example, nerve regeneration. Recently, an animal study with efferent neuron staining showed absence of regeneration up to 640 days after TLD treatment [19]. Interestingly, the bronchodilator response to LAMA was maintained after TLD in COPD patients, and therefore TLD could be considered an add-on treatment instead of replacement of LAMA therapy [20].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Following TLD, studies have shown a decrease in the axonal staining by approximately 60% to 70%, distal to the ablation site at 30 days, while effectively protecting peri-bronchial structures and the perioesophageal vagal nerve branches. This effect on efferent axon staining was demonstrated at 365 and 640 days, indicating a durable effect [41]. Transcriptomic analyses of airway mucosal brush samples collected at 3-month post-TLD, have shown a reduced expression of acetylcholine related genes [42 && ].…”
Section: Targeted Lung Denervationmentioning
confidence: 99%